Jeune syndrome in a pediatric patient: A clinical case report - Zapata Aguilar, Elert (2018)
Jeune syndrome is a low frequency, autosomal recessive and potentially life-threatening skeletal dysplasia. From a clinical perspective, it has a wide variety of manifestations; however, it is commonly characterized by a narrow thorax; secondary pulmonary hypoplasia; brachymelia; and pelvic, cardiac and renal abnormalities. Lung involvement is variable and may be lethal. The diagnosis may be suspected prenatally through an ultrasonography, by measuring the thoracic and rib cage circumference, and studying the relation between them and with the abdominal circumference. This article describes the clinical case of a 3-month-old female patient with a mild disease presentation and postnatal diagnosis.